Trunk kinematics in the sliding forehand on clay courts: a comparison of elite and sub-elite tennis players - Chang, K.-L.; Tang, W.-T.; Huang, T.-Y.; Lin, Z.-J.; Hsiao, C.-Y. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study compares the trunk kinematics of elite and sub-elite male tennis players during the sliding forehand stroke on clay courts. A total of 24 highly skilled players participated in this study. Their stroke execution was recorded using a 3D high-speed infrared motion capture system. Independent sample t-tests (p < 0.05) were used to compare trunk kinematics between groups. Elite players outperformed their sub-elite counterparts across all measured points, including greater right lateral bending at the Ground Contact and End Backswing points, enhanced anterior tilt at the Impact and Racket Extension points, and superior left lateral bending at the Completion of Swing point. Additionally, their greater maximum trunk displacement reflects superior trunk control and movement efficiency throughout the stroke sequence. This study underscores the importance of trunk rotational control and sliding techniques in optimizing forehand performance on clay courts.